Digitalisation and Employees' Subjective Job Quality in the Second Half of Working Life in Germany - Lisa Katharina Kortmann; Julia Simonson; Claudia Vogel; Oliver Huxhold (Social Indicators Research, 2021)
Since digitalisation alters occupational task profiles via automation processes, job quality is also likely to be affected. While existing literature mainly focusses on objective job quality, this study asks if and how digitalisation is associated with employees' subjective job quality in the second half of working life in Germany. Analyses are based on the German Ageing Survey 2014. Our sample includes n0.167em=0.167em1541 employees aged 40–65~years who are subject to social insurance contributions. Subjective job quality is operationalised with regards to job satisfaction and perceived occupational stress in general, and ten aspects of job quality in detail. Digitalisation is approximated by substitution potentials of occupations. We control the association for compositional effects in the workforce, as well as for the moderating effect of perceived job insecurity. The results indicate that digitalisation is predominantly beneficial but also unfavourable in a few other respects for employees' subjective job quality. The higher the degree of digitalisation, the higher is the employee's general job satisfaction on average; for general perceived occupational stress, we find no significant association. Regarding single aspects of subjective job quality, employees working in more digitalised occupations are found to report on average higher satisfaction with working hours and earnings, and lower levels of stress due to tight schedules. However, they also report higher levels of stress due to negative environmental factors.
Keywords: 300; Job satisfaction; Occupational stress; Subjective job quality; Digitalisation; German Ageing Survey